Influence of the habitat on the potential for cannibalism and population dynamics in stream-dwelling European grayling (Thymallus thymallus L.) - Lindström, Carl-Johan (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2010)
Cannibalism can have major influence on fish population dynamics. A prerequisite for cannibalism is that the cannibal and the potential victim meet, and besides density effects, the encounter rate between cannibals and their victims is therefore also largely dependent on habitat use and habitat heterogeneity. In this study I quantified and compared the potential for cannibalism in stream-dwelling European grayling populations in three rivers in Jämtland by means of habitat classifications. I also analyzed population dynamic consequences of varying the potential for cannibalism in terms of intensity, using a physiological structured population model. Findings based on habitat characteristics were that the potential for cannibalism is in general not favourable in these types of streams. However, some sections had optimal conditions for cannibalism. The population dynamic model predicted that cannibalism can regulate the dynamic if sufficiently intense. It might also induce population cycles, and a fishing mortality will increase the destabilizing effect. It is the younger cohorts that drive the cycles by delayed density regulation. Cannibalism can be important to take into consideration in management actions. Hence, sections with favorable conditions for cannibalism also has a capacity for high fish production, and can thus be important as a source to less productive areas of a watercourse. Cannibalism can therefore indirectly decrease the fish density in more sections than in the few sections with favorable conditions for cannibalism. Moreover, if a population has fluctuating dynamics, some years the population will be dominated by young individuals, which not is desirable for watercourses used for sportfishing.